ENDOMARKETING AND ITS PRACTICE IN ORGANIZATIONS - Gonçalves Soares Campos, Lucas (Revista Gênero e Interdisciplinaridade, 2022)
The objective of this study is to visualize and understand the effectiveness of Endomarketing as a path used to overcome the challenges faced in organizations to direct their team of collaborators. In this way, the bibliographical review and the study to be developed on the selected companies will seek to contribute information on the universe of Endomarketing and its reality in a business environment, seeking to identify the main effects and consequences achieved in all its phases. Based on a set of authors, bibliographical references and interviews, it aims to complement the debate on the benefits of implementing endomarketing in organizations and its practical effects on institutional employees, analyzing how endomarketing strategies can impact organizations/employees and add value to its results and in the motivation/domination of its employees.